The Use of the Artificial Neural Network (ANN) Method to Forecast the Performance of Solar Collector Systems (International Journal of Innovative Research in Engineering & Management, 2021)
Whatever wind and solar collection device designed to work  mostly in low to mid-temperature area. Must include a solar  collector at its core. As a result, an efficient solar collector  system design with optimal performance is needed. Intelligent  system design is a helpful method for optimizing the  efficiency of such systems, even if many other strategies are  used to improve system performance. Artificial Neural  Network (ANN) is a kind of intelligence method that is  utilized in system modeling, simulation, and control. In  comparison to other traditional methods, the ANN tool solves  difficult and nonlinear problems quicker and more accurately.  The artificial neural network (ANN) method Economics,  economics, art, military, trade, and technology are just a few  of the sectors where it's applied. Our ANN tool's main task is  model building, which will be done with the use of empirical  observations. From solar energy systems, and this technique  does not need separate programming like other traditional  methods. The goal of this research is to look at how artificial  intelligence (AI) may be used to forecast to assess the  effectiveness of wind and solar collections and to review  relevant requirements for the proposed study this same ANN  approach is an excellent tool for forecasting solar panel  function. Collector systems, as shown by the study reported in  this article.
Keywords: Artificial Neural Network; Learning Algorithm; Multi-layer perceptron Thermal performance; Solar energy collector